A Comprehensive Assessment of Ayurvedic Patient Care Services in a Modern Medicine Public Tertiary Care Hospital - Renuka Munshi; Santosh Kadam (RGUHS Journal of AYUSH Sciences)
Introduction The integration of traditional and complementary medicine with modern healthcare systems has emerged as a significant challenge for numerous countries driven by the growing popularity of diverse medical practices and the need to control healthcare expenditures. This study endeavours to comprehensively assess Ayurvedic patient care services within a public tertiary care hospital that predominantly delivers modern medicine. Given the escalating recognition of traditional medicines potential to complement conventional healthcare understanding the utilization and outcomes of Ayurveda in this context assumes paramount importance.Methods A retrospective analysis covering the past five years was performed to investigate the demographics disease patterns and use of Ayurvedic treatments among patients receiving care at the hospital. Data on patient retention and the seamless integration of Ayurveda with modern medicine were thoroughly examined.Result The study identified a significant rise in the use of Ayurvedic patient care services predominantly among female patients aged 19-40 years. Over five years patient retention rates exhibited a gradual increase signifying a higher level of patient satisfaction and loyalty towards Ayurvedic treatments. Among the ailments treated musculoskeletal disorders gastrointestinal issues and dermatological conditions ranked as the most commonly addressed health concerns. Notably Ayurvedic medicines in the form of Rasa Aushadhi herbomineral preparations emerged as the predominant therapeutic modality. Conclusion The studys findings underscore the growing popularity of Ayurvedic patient care services and their potential to complement modern medicine. Effective Ayurveda integration requires understanding patient preferences and disease patterns to optimize healthcare services and bridge the gap between traditional and modern medicine.